Settlement Phenotypes: Social Selection and Immigration in a Common Kestrel Population - Fargallo, Juan Antonio; López-Rull, Isabel (Frontiers in Ecology and Evolution, 2022)
Dispersal decisions are affected by the internal state of the individual and the external environment. Immigrants entering a new population are phenotypically different from residents due to selection that mitigate costs of dispersal and facilitate settlement. Sexual and social status traits may influence individual´s ability to settle in a population, either by showing a subordinate phenotype thus reducing aggressive interactions, or by signaling a more competitive phenotype, thus gaining local breeding resources, including mates. By comparing immigrants vs. residents in a common kestrel population across 17 years, we evaluated the influence of dispersal on fitness components (laying date, clutch size and number of fledglings) and investigated if the individual phenotype (sex, age, body size, feather length, body condition and plumage coloration) involved in movement and social interactions and population characteristics (mean clutch size, density and growth) affected settlement. We found that population characteristics affected sexes and age classes differently, as the admission of females and young males into our population had fewer obstacles than the admission of adult males. In females, immigrant young were larger, had longer wings and tails, showed better body condition, had less grey tails, started breeding earlier and laid larger clutches than residents. Adult female immigrants also showed better body condition and less grey tails. In males, immigrants had longer tails and higher number of back spots than residents. Summarizing, immigrants are good-quality individuals and, as deduced from their breeding performance, they benefited by signaling subordination, thus reducing the probability of aggressive encounters and facilitating settlement. Our study highlights the role of phenotypic traits related to signaling to study dispersal.